Representasi Ideologi Patriarki pada Film Suzanna : Malam Jumat Kliwon (2023) - Nadhirah Hasna , Aulia; Puspita Tutiasri , Ririn (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Film serves not only as a medium of entertainment but also as a form of mass communication that represents and reproduces social ideologies, including patriarchal ideology. Suzanna:MalamJumat Kliwon (2023)portrays various power relations that demonstrate male dominance over women in both domestic and social contexts. This study aims to analyze the representation of patriarchal ideology in the film. The research employed a qualitative approach using John Fiske's semiotic analysis through three analytical levels: reality, representation,and ideology. Data were collected through observations of eight scenes depicting patriarchal practices and supported by relevant literature. The findings reveal that patriarchal ideology is represented through four main aspects: (1) control over women's life choices, (2) objectification of women's bodies and reproductive functions, (3)male domination and gender-based violence, and(4) the silencing of women's voices in decision-making. These representations are constructed through dialogue, facial expressions, gestures, cinematographic techniques, lighting, and visual composition that consistently portray unequal power relations between men and women. The study concludes that Suzanna: Malam Jumat Kliwon (2023) represents patriarchy as a social system that legitimizes male dominance through normalized practices in both domestic and social life, thereby restricting women's rights, autonomy, and agency.